Dampak Pembuangan Sampah Rumah Tangga di Pinggir Jalan Terhadap Lingkungan di Kp. Pakuwon - Ageng Saepudin Kanda S; Dikdik Jamaludin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Garbage or household waste is waste that comes from people's daily activities, especially the result of leftover food, food wrappers that are no longer needed, this waste will have an impact on the environment if it is not managed properly or may even become a problem in that environment. The aim of this research is to find out the impact that will occur from the disposal of rubbish or household waste that is dumped on the side of the road in Pakuwon Village, Jati Village, Saguling District, West Bandung Regency. The research method used is a descriptive qualitative research method, where the data produced is a description of the results of observations at the location and the results of interviews with the surrounding community who are the objects as sources. From the results of observations made, the impacts caused by the disposal of household waste include polluting the environment, causing unpleasant odors from the waste and reducing the comfort level of people who pass through the road and even the residents themselves are uncomfortable because of the smell. very stinging especially when it rains.